Effects of the combination of compression and impregnation with phenolic resin on the dimensional stability in the multiscale wood structure of Chinese fir. (11th April 2022) - Wang, Junfeng; Yao, Yan; Huang, Yaqian; Ma, Yingjie; Xi, Jingyu; Wang, Xinzhou; Li, Huaguan; Yang, Zhangqi
Highlights: The distribution of phenolic resin in wood cell lumen was calculated by microscopic images processing. The expansion properties of modified wood cells were also discussed by image processing. The interactions between resin and cells were analyzed to indicate the fixation mechanism of compressed wood on cell-level. Promotion a precise, directional and controllable modification for fast-growing wood. Abstract: Chinese fir wood was pretreated by phenol–formaldehyde (PF) resin and followed by the compression along the radial direction at the compression ratio of 10%, 20% and 30%, respectively. The microscopic images of the control and modified wood at different humidity were then collected to evaluate the dimensional stability of wood cellular structures. The interactions between the cell wall and resin were also observed by SEM and Raman spectroscopy to reveal the fixation effects of resin on the compressed wood at cell-level. Results indicated that the number of wood cells filled with PF resin increased significantly with the increase of impregnation pressure and processing time, which contributed to an obvious decrease in the linear and volumetric expansion ratio of wood at high humidity, in particular at the RH of 90%. The filling of PF resin in the wood cell lumen and the open pits on the tracheid walls not only inhibited the entry of water molecules but also had a chemical interaction with cell-wall, which could significantly reduce the set-recovery of the compressed wood. The radial expansion ratio of wood at a compression ratio of 30% has been reduced by about 65% at the RH of 90% after PF resin impregnation.